Quantitative assessment of driving performance in Parkinson's disease. Issue 2 (14th January 2005) - Wood, J M; Worringham, C; Kerr, G; Mallon, K; Silburn, P
Abstract : Objectives: The primary aim of this study was to determine how Parkinson's disease (PD) affects driving performance. It also examined whether changes in driver safety were related to specific clinical disease markers or an individual's self rating of driving ability. Methods: The driving performance of 25 patients with idiopathic PD and 21 age matched controls was assessed on a standardised open road route by an occupational therapist and driving instructor, to provide overall safety ratings and specific driving error scores. Results: The drivers with PD were rated as significantly less safe (p<0.05) than controls, and more than half of the drivers with PD would not have passed a state based driving test. The driver safety ratings were more strongly related to disease duration ( r = −0.60) than to their on time Unified Parkinson's Disease Rating Scale ( r = −0.24). Drivers with PD made significantly more errors than the control group during manoeuvres that involved changing lanes and lane keeping, monitoring their blind spot, reversing, car parking, and traffic light controlled intersections. The driving instructor also had to intervene to avoid an incident significantly more often for drivers with PD than for controls. Interestingly, driver safety ratings were unrelated to an individual's rating of their own driving performance, and this was the case for all participants. Conclusions: As a group, drivers with PD are less safe to drive than age matched controls. Standard clinical markers cannot reliably predict driver safety. Further studies are required to ascertain whether the identified driving difficulties can be ameliorated.